Technical Problems and Political Uses of National Assessments in the Argentinian Educational System - Gvirtz, Silvina; Larripa, Silvina; Oelsner, Verónica (Education Policy Analysis Archives, 2006)
This article presents results from different research investigations which have explored the relations between the technical and the political dimension of the assessment of educational systems. The case study taken on for this matter is the national evaluation system in force in Argentina since 1993. In the first part we present some technical problems which the implementation of this system has encountered in this country. In the second part we carry out an analysis of these technical inconveniences, within the political context of educational reform in which the evaluation system arises and develops. In addition, we present an analysis of the effective use of the information provided by the evaluations. Finally, in the conclusions, we present some considerations on the role of national evaluations in educational reform contexts, and on the prospects of their consolidation as systems which inform in a valid and reliable form about the course of education in the mid and long term.